Health-Sector Responses to Intimate Partner Violence: Fitting the Response Into the Biomedical Health System or Adapting the System to Meet the Response?. Issue 10 (May 2018) - Briones-Vozmediano, Erica; Maquibar, Amaia; Vives-Cases, Carmen; Öhman, Ann; Hurtig, Anna-Karin; Goicolea, Isabel
This study aims to analyze how middle-level health systems' managers understand the integration of a health care response to intimate partner violence (IPV) within the Spanish health system. Data were obtained through 26 individual interviews with professionals in charge of coordinating the health care response to IPV within the 17 regional health systems in Spain. The transcripts were analyzed following grounded theory in accordance with the constructivist approach described by Charmaz. Three categories emerged, showing the efforts and challenges to integrate a health care response to IPV within the Spanish health system: "IPV is a complex issue that generates activism and/or resistance, " "The mandate to integrate a health sector response to IPV: a priority not always prioritized, " and "The Spanish health system: respectful with professionals' autonomy and firmly biomedical." The core category, "Developing diverse responses to IPV integration, " crosscut the three categories and encompassed the range of different responses that emerge when a strong mandate to integrate a health care response to IPV is enacted. Such responses ranged from refraining to deal with the issue to offering a women-centered response. Attempting to integrate a response to nonbiomedical health problems as IPV into health systems that remain strongly biomedicalized is challenging and strongly dependent both on the motivation of professionals and on organizational factors. Implementing and sustaining changes in the structure and culture of the health care system are needed if a health care response to IPV that fulfills the World Health Organization guidelines is to be ensured.